Nieczajew a Bakunin - Kamiński, Antoni A. (Nechaev and Bakunin, 2007)
The article discusses in detail M. Bakunin’s and S. Nechaev’s two years co-operation (1869- -1870). The author also analyzes reasons for Nechaev’s intellectual influence on Bakunin’s thoughts. In the last part of the article, the author defines term “nechaevism” nad points out its manifestations in the Russian revolutionary movement.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (11); 2007; nr 1188, s. 159-202